Utilization of extracellular polymeric substances (EPS) immobilized in epoxy polymer as double ion exchanger biosorbent for removal of chromium from aqueous solution - Kistriyani, Lilis; Salimin, Zainus; Chafidz, Achmad (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2020)
Cation and industrial pollutant anions are removed from wastewater using organic cation and anion exchange resin.